2021
DOI: 10.1186/s12891-021-03982-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of high-frequency ultrasound and virtual touch tissue imaging and quantification improve the diagnostic efficiency for mild carpal tunnel syndrome

Abstract: Background Carpal tunnel syndrome (CTS) is the most common entrapment symptom in the peripheral nerves. High-frequency ultrasound (HFUS) is widely used in the diagnosis of CTS. Virtual Touch Tissue Imaging and Quantification (VTIQ), which provides more information about the hardness of organization, is used to diagnose CTS. However, the data of diagnostic value of them in various degrees of CTS are limited. Whether the combination of HFUS and VTIQ can improve the diagnostic efficiency also rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Moreover, recent advancements in imaging techniques, including high-resolution ultrasound and magnetic resonance imaging (MRI), have contributed to enhanced diagnostic accuracy ( 67 ). Ultrasound can visualize median nerve morphology and quantify its cross-sectional area, thus providing valuable anatomical information ( 68 ) while MRI offers the advantage of assessing soft tissue structures within the carpal tunnel, including ligaments and tendons ( 67 ). Table 4 provides an overview of the clinical manifestations and diagnostic indicators associated with Carpal Tunnel Syndrome (CTS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent advancements in imaging techniques, including high-resolution ultrasound and magnetic resonance imaging (MRI), have contributed to enhanced diagnostic accuracy ( 67 ). Ultrasound can visualize median nerve morphology and quantify its cross-sectional area, thus providing valuable anatomical information ( 68 ) while MRI offers the advantage of assessing soft tissue structures within the carpal tunnel, including ligaments and tendons ( 67 ). Table 4 provides an overview of the clinical manifestations and diagnostic indicators associated with Carpal Tunnel Syndrome (CTS).…”
Section: Resultsmentioning
confidence: 99%
“…Proactive workplace strategies, including ergonomic modifications, regular breaks for hand and wrist stretches, prove to be crucial in mitigating the risk of Carpal Tunnel Syndrome (CTS). Employing ergonomic principles, equipment modification, and task rotation, can help decrease the risk of CTS by reducing strain on the hands and wrists ( 68 ). Importantly, promoting awareness and providing education on proper ergonomics and hand hygiene practices can significantly contribute to prevention efforts in high-risk occupational settings ( 68 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic tests evaluated and their weighted mean sensitivity and specificity are outlined in Tables 2 and 3. 16-128 Although studies utilizing “clinical diagnosis” as a reference standard were treated as a unified subset, many studies 16-128 were found to utilize different definitions of clinical diagnosis. An outline of the utilized definitions for “clinical diagnosis” is presented in Supplemental Digital Content 1.…”
Section: Resultsmentioning
confidence: 99%
“…It is a complement to conventional ultrasound in the assessment of neuropathy (18)(19)(20)(21). Studies have reported the significance of elastography in the assessment of CTS (22)(23)(24)(25). However, to the extent of our knowledge, there are few reports on the evaluation of pre-and post-operative changes in nerve stiffness in patients with CTS.…”
Section: Introductionmentioning
confidence: 99%